A pilot study comparing pulse high volume hemofiltration (pHVHF) and coupled plasma filtration adsorption (CPFA) in septic shock patients - Lentini, P; Cruz, D; Nalesso, F; de Cal, M; Bobek, I; Garzotto, F; Zanella, M; Brendolan, A; Piccinni, P; Ronco, C (Giornale italiano di nefrologia, 2009)
High-volume hemofiltration (HVHF) and coupled plasma filtration adsorption (CPFA) have shown potential to improve the treatment of sepsis in animals, but there have been no studies comparing these two treatments in humans. Our aim was to compare the hemodynamic effects of HVHF and CPFA in septic shock patients with acute kidney injury (AKI) undergoing continuous renal replacement therapy (CRRT). We performed a cross-over study enrolling patients with septic shock and AKI who were receiving CRRT. Patients were treated with pulse HVHF and continuous veno-venous hemofiltration (CVV H) on day 1 and CPFA and CVV H on day 2 or vice versa. HVHF was performed for 8-10 hours with a replacement fluid rate of 85 mL/kg/h. CPFA was performed for 8-10 hours with a plasma flow rate of 15%. CVV H was performed for the rest of the day with a replacement fluid rate of 35 mL/kg/h. The primary endpoints were changes in mean arterial pressure, vasopressor requirement (expressed as vasopressor score, VS), and noradrenaline dose after pulse HVHF and CPFA. The two treatments were compared using nonparametric tests. We enrolled 8 patients (median age 70.5 years, SOFA 12.5, SAPS II 69.5). There was a trend towards a reduction in VS with HVHF and CPFA (HVHF p=0.13, CPFA p<0.05). There was no significant difference between the two treatments in terms of percentage change in VS score (p=0.22). The data from this pilot study provide no evidence for a difference in hemodynamic effects between pulse HVHF and CPFA in patients with septic shock already receiving CRRT. A larger sample size is needed to adequately explore this issue.